PENGARUH MUTASI, PROMOSI JABATAN DAN KEPUASAN KERJA TERHADAP PRESTASI KERJA PEGAWAI KEMENTERIAN SOSIAL REPUBLIK INDONESIA - Irawati Kusuma Dirja; Dr. Ismail Razak, M.Si. (Jurnal Manajemen Bisnis Krisnadwipayana, 2020)
The aim of this study was to analize the effect of mutation, job promotion, and job satisfaction on the achievement of employee of the Ministry of Social Affairs of the Republic of Indonesia. Primary data was obtained from employee of the Ministry of Social Affairs of the Republic of Indonesia through admission filling of questionnaire by using scale of Likert. Data analysis technique used in this research is simple linear regression and multiple linear regression. The results of this study indicated that mutation, job promotion, and job satisfaction positively and significant influenced the achievement of employee of the Ministry of Social Affairs of the Republic of Indonesia.